The Effectiveness of Lavender Aromatherapy in First Trimester Pregnant Women with Emesis Gravidarum at TPMB Megawati in 2023 - Olivia Nency; Megawati Megawati (CV. Inara, 2024)
Background: Pregnant women with emesis gravidarum who use acupressure can reduce or even avoid the use of anti-nausea drugs which have the potential to have side effects. This can be considered as an effective non-pharmacological alternative in treating emesis gravidarum. Purpose of Writing: Knowing the Effectiveness of Lavender Aromatherapy in First Trimester Pregnant Women with Emesis Gravidarum at TPMB Megawati in 2023. Research Method: quasi-experimental research with pretest posttest with control group design. The independent variable in this study was lavender aromatherapy and the dependent variable was Emesis Gravidarum. taken by purposive sampling. Data analysis was carried out univariately and bivariately, to find out the difference in the Emesis Gravidarum score in the intervention and control groups in each group using wicoxo. Research Results The research results are known Asymp. Sig (2 – Talled) has a value of 0.000 because 0.000 <0.05, it can be concluded that the hypothesis is accepted. This means that there is a difference before and after giving lavender aromatherapy. The research results are known Asymp. Sig (2 – Talled) has a value of 1,000 because 0.000 > 0.05, it can be concluded that the hypothesis is rejected. This means that there is no difference before and after in the control group.